ANALISIS DAYA SAING EKSPOR DAN DETERMINAN EKSPOR KARET ALAM INDONESIA DI 10 NEGARA TUJUAN EKSPOR UTAMA 2007 â 2012 - , MA'RUFUL MUSTHOFA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Natural rubber is a commodity plantations Indonesiaâs second largest export after oil palm. This study purposes is to analyze the competitiveness of Indonesiaâs natural rubber exports and the factors that affect Indonesiaâs natural rubber exports to 10 major export destinations. Revealed Symetric Comparative Advantage (RSCA) and Trade Balance Index (TBI) are an analytical tools to determine the competitiveness of Indonesiaâs natural rubber exports. The results showed that Indonesiaâs natural rubber has high comparative advantage and Indonesia as net exporter of natural rubber. While the panel data regression models using a fixed effect model on 10 main export destinations showed that natural rubber prices, national income, the exchange rates, and preference of the country of export destinations has significant effect on Indonesiaâs natural rubber exports.